(untitled) (Agroindustrial Science, 2025)
The objective of this research was to determine the effect of including phytase in the feed of broiler chickens. During seven weeks, 192 Ross broilers were evaluated, applying six treatments with four replicates of eight birds each. Treatments included different levels of phytase Ronozyme Np (4% to 12%) and a phytase-free control. Parameters such as feed intake, weight gain, feed conversion, carcass yield, mortality and economic efficiency were measured. In the initial phase, the control treatment obtained the greatest weight gain (631 g), while in the final phase T3 (993.75 g) stood out and in the total phase T4 (2604.25 g). Feed intake did not show differences in the initial phase, but in the final phase T3 and T4 were the most efficient. Daily weight gain was greatest at T2, T3, and T6 (137 g). The best feed conversion was obtained at T1 (1.25 kg). In carcass performance, T3 and T6 obtained the best values without significant differences. Mortality was low in all groups, with T1 registering 0.52%. In terms of profitability, T4 (8% phytase) showed the best benefit-cost ratio. These results indicate that the inclusion of phytase in the diet improves productive performance and profitability in broilers.